Extraction, Characterization, and Optimization of Protein From Food Waste and Waste-Activated Sludge - Cheruiyot Dennis; Seth Apollo; George Simba Nyamato (Journal of Chemistry)
There is a growing interest in the recovery of valuable biomaterials from waste in line with reaping the benefits of a circular economy. Organic wastes, such as waste-activated sludge (WAS) and food waste (FW), contain a substantial amount of protein that can be recovered for various applications. This study compared thermal alkaline and acid hydrolysis methods for their efficiencies in extracting protein from FW and WAS. The possibility of enhancing protein yield and quality through co-extraction of WAS and FW was also investigated. Response surface methodology was used to optimize the extraction process. Before extraction, WAS was purified by removing heavy metals using acid pretreatment. It was established that FW had 21.5 g/100 g protein, while WAS had 19.9 g/100 g protein. The two extraction methods had superior extraction for WAS as compared to FW. In addition to this, there was no significant increase in protein yield in the co-extraction of protein from the FW and WAS mixture. Furthermore, optimization using RSM showed that the optimal yield of 15.8 g/100 g was obtained at a pH of 13 and a temperature of 120°C, close to the experimental yield of 16.6 g/100 g WAS. Moreover, LC–MS analysis of the extracted protein showed that WAS had a good essential amino acid profile with threonine, lysine, leucine, methionine and valine in concentrations of 3.3, 2.7, 1.8, 1.1, and 2.7 g/100 g, respectively. Significantly, the level of threonine revealed the potential of beneficiation of WAS as an animal food supplement because threonine plays an important role in the synthesis of mucosal protein that lines and protects the intestinal tract as well as modulation of nutritional metabolism and macromolecular biosynthesis in animals. In addition to that, the ratio of the first limiting amino acids (lysine and methionine) met the standards for animal feed supplementation.